Building and dismantling organisational capacity and bureaucratic identity: an analysis of Ibama’s civil service examinations (1989 – 2022) - Moulin, Carolina Stange Azevedo (Sustainability in Debate, 2023)
This article investigates how the recruitment procedures for the selection of environmental inspectors in Ibama, Brazil’s leading federal environmental agency, have varied since the institution’s creation in 1989 until 2022. To explain the identified changes, the study considers the organisation’s accumulated experience and political context. It draws on 44 semi-structured interviews and analyses the content of all five examination booklets (caderno de questões) and their corresponding calls (editais) for the position of environmental analyst organised during Ibama’s history, with a focus on the subtopic “Regulation, Control, and Environmental Inspection”. For interpreting this data, I mainly used qualitative content analysis. I coded the data based on the following categories: eligibility requirements, regional allocation criteria, programmatic content, general structure of the exam, individual motivation to become an Ibama servant, impact of public exams on inspection activities, and impact of the political context on inspection activities. Exam booklets went through an additional quantitative analysis on the number of references to “deforestation”, “Amazon”, and “inspection”. My findings suggest that Ibama’s examinations between 2002 and 2013 reflect an incremental process of specialisation and technicalisation. This process enhanced the agency’s capacity to inspect deforestation and strengthened its identity around the ideal of environmental stewardship. In an attempt to fracture Ibama’s capacity and identity, the 2021 examination prompted a deliberate shift in selected candidates’ profiles.